"Ni oirlos ni decirlos". Where secrets awaits, approximate to the concept of early modern family - Fargas Peñarrocha, Mariela (Cuadernos de Historia Moderna, 2015)
This text is about the practices and emotions that build the secret or secrets in the everyday life in early modern history. The sinuosity of its existence leads historians to research the relationship between people, because the secret not exist outside them, as a space reserved, desire for protection and behavioural strategy. So the issue is important in a context of opposing elements, compared to the rest, to the public and to the normalized. In this sense the secret should contribute to the knowledge of the dualities and contradictions in the family, and is her political and moral building element.